Increases in a Pro-inflammatory Chemokine, MCP-1, Are Related to Decreases in Memory Over Time - Bettcher, Brianne M.; Neuhaus, John; Wynn, Matthew J.; Elahi, Fanny M.; Casaletto, Kaitlin B.; Saloner, Rowan; Fitch, Ryan; Karydas, Anna; Kramer, Joel H. (Frontiers in Aging Neuroscience, 2019)
Objective: To determine the longitudinal relationship between MCP-1/CCL2 and memory function in older adults. Methods: We examined longitudinal plasma MCP-1/CCL2 levels and a longitudinal verbal memory measure (CVLT-II 20’ recall) in a sample of 399 asymptomatic older adults (mean age=72.1). Total visits ranged from 1 to 8, with an average time of 2.1 years between each visit, yielding 932 total observations. In order to isolate change over time, we decomposed MCP-1/CCL2 into subject-specific means and longitudinal deviations from the mean. The decomposed MCP-1/CCL2 variables were entered as predictors in linear mixed effects models, with age at baseline, sex, and education entered as covariates and recall as the longitudinal outcome. In follow-up analyses, we controlled for global cognition and APOE genotype, as well as baseline vascular risk factors. We also examined the specifity of findings by examining the longitudinal association between the MCP-1/CCL2 variables and non-memory cognitive tests. Results: Within-subject increases in MCP-1/CCL2 levels were associated with decreases in delayed recall (t=-2.65; p=.01) over time. Results were independent of global cognitive function and APOE status (t=-2.30, p=.02), and effects remained when controlling for baseline vascular risk factors (t=-1.92, p=.05). No associations were noted between within-subject increases in MCP-1/CCL2 levels and other cognitive domains. Conclusions: In an asymptomatic aging adult cohort, longitudinal increases in MCP-1/CCL2 levels were associated with longitudinal decline in memory. Results suggest that ‘healthy aging’ is typified by early remodeling of the immune system, and that the chemokine, MCP-1/CCL2, may be associated with negative memory outcomes.